GE_GERICHTE C/29229/2018 vom 21. Juni 2019 - GE Cour de justice (2019)
DROIT D'AUTEUR ET DROITS VOISINS;SOCIÉTÉ DE GESTION;COPIE;TARIF(EN GÉNÉRAL);INTÉRÊT MORATOIRE | LDA.59.al1; LDA.59.al3; LDA.62.al2; CO.102.al2; CO.104.al1